PENGARUH PENERAPAN LATIHAN TENDANGAN BOLA BERGERAK DAN TENDANGAN BOLA TETAP TERHADAP HASIL TENDANGAN KE GAWANG PEMAIN SEKOLAH SEPAK BOLA RBS - Suherman, Senga; Jalil, Rasyidah; Kahar , Irsan; Burhan, Ahmad Syarif; Riswanto, Ahmad A.Heri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In soccer, the ability to kick on goal is a fundamental skill that significantly determines the effectiveness of an attack. This study aims to determine the effect of moving and fixed ball kick training on goal kicking skills in RBS Soccer School players. This study used an experimental design with a two-group pretest-posttest design. The sample consisted of 34 players aged 13–15 years, divided into two experimental groups. The first group received moving ball kick training, while the second group received fixed ball kick training, each for 16 training sessions. Data were collected through observation and skill tests, and analyzed using normality tests, homogeneity tests, and paired sample t-tests. The results showed that moving ball kick training significantly improved goal kicking results compared to fixed ball training. The average post-test score for the moving ball group (10.20) was higher than that for the fixed ball group (9.00), with kicking performance improvements of 50% and 47.5%, respectively. Thus, moving ball kicking practice is more effective in improving goal-kicking skills in RBS Soccer School players.